PTERIDOPHYTE FLORA ALONG THE STRETCHES OF THE THAMIRAPARANI RIVER (WEST), KANNIYAKUMARI DISTRICT, TAMIL NADU, INDIA (International Journal of Food and Nutritional Sciences, 2023)
An extensive floristic survey was conducted along the downstream stretches of the Thamiraparani River in Kanniyakumari District, Tamil Nadu, to document the pteridophyte diversity in the region. Between July 2019 and March 2020, a total of 64 pteridophyte species, representing 41 genera and 14 families, were recorded. The survey revealed a rich and diverse assemblage of pteridophytes, highlighting the ecological significance of the river ecosystem in supporting a variety of plant species. Specimens were identified with the aid of regional floras, and voucher specimens were deposited in the herbarium of Nesamony Memorial Christian College, Marthandam, for future reference. The results provide a valuable baseline for understanding the pteridophyte flora of the Thamiraparani River and contribute to the broader knowledge of plant diversity in the southern Western Ghats, an area known for its high biodiversity but relatively understudied pteridophytic flora. The findings underscore the need for further research and conservation efforts to preserve the rich botanical heritage of this unique ecosystem.